2019
DOI: 10.3390/ma12030413
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Fe2O3–SiO2–MeO2–Pt (Me = Ti, Sn, Ce) as Catalysts for the Selective Hydrogenation of Cinnamaldehyde. Effect of the Nature of the Metal Oxide

Abstract: The type of metal oxide affects the activity and selectivity of Fe2O3–SiO2–MeO2–Pt (Me = Ti, Sn, Ce) catalysts on the hydrogenation of cinnamaldehyde. The double shell structure design is thought to protect the magnetic Fe2O3 cores, and also act as a platform for depositing a second shell of TiO2, SnO2 or CeO2 metal oxide. To obtain a homogeneous metallic dispersion, the incorporation of 5 wt % of Pt was carried out over Fe2O3–SiO2–MeO2 (Me = Ti, Sn, Ce) structures modified with (3-aminopropyl)triethoxysilane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The Langmuir–Hinshelwood (L-H) adsorption kinetic model has been widely adopted for studies of the reaction of CAL hydrogenation over catalysts. For a batch reactor system, the reaction rates fit to the first-order reaction with respect to H 2 pressure over Pt, , Pd, Ni, , Co, and Ir-based catalysts, indicating a zero-order dependence on CAL concentration. The concentration of H 2 in the solvent dominates the reaction rate, and the solvent with higher solubility of H 2 will promote the reaction rate.…”
Section: Kinetic Study Of Cal Hydrogenationmentioning
confidence: 99%
“…The Langmuir–Hinshelwood (L-H) adsorption kinetic model has been widely adopted for studies of the reaction of CAL hydrogenation over catalysts. For a batch reactor system, the reaction rates fit to the first-order reaction with respect to H 2 pressure over Pt, , Pd, Ni, , Co, and Ir-based catalysts, indicating a zero-order dependence on CAL concentration. The concentration of H 2 in the solvent dominates the reaction rate, and the solvent with higher solubility of H 2 will promote the reaction rate.…”
Section: Kinetic Study Of Cal Hydrogenationmentioning
confidence: 99%
“…Pt nanoparticles were introduced to the surface of the double-shell-coated Fe 2 O 3 nanoparticles . Two shells can greatly protect the Fe 2 O 3 nanoparticles.…”
Section: Applications Of Magnetic Nanomaterials In Heterogeneous Cata...mentioning
confidence: 99%
“…Pt nanoparticles were introduced to the surface of the doubleshell-coated Fe 2 O 3 nanoparticles. 88 Two shells can greatly protect the Fe 2 O 3 nanoparticles. Dinamarca et al demonstrated that Fe 2 O 3 −SiO 2 −CeO 2 −Pt showed high selectivity to COL for the hydrogenation of CAL, where CeO 2 as the second shell can control the configuration of Fe 2 O 3 −SiO 2 .…”
Section: Acs Applied Nano Materialsmentioning
confidence: 99%